PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN GO PUBLIC DI INDONESIA DAN THAILAND - Rahmah, Yulina; Rahmawati, Vince; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to examine the effects of Sustainability report diclosure on the company’s financial performance which are meaasured by profitability, liquidity, and dividend payout ratio. Independet variables used in this study is the Sustainability Report disclosure which was measured by using the GRI (Global Reporting Initiatives) index. The dependent variables used were Return on Assets (ROA), cureent ratio (CR) and Dividend Payout Ratio (DPR). The samples of this research are the firms listed in Indonesia Stock Exchange and Stock Exchange of Thailand and the firm that revealed Sustainability Report in 2012-2016. The sample are collected using purposive sampling method and resulted 12 firms from Indonesia dan 18 firms from Thailand and totaliy is 30 firms becomes the samples.To test the hypothesis the data was analyzed by using SmartPLS 3.0. The result show that in Inodenesia sample the Sustanability Report dislosure positivelty influences ROA, CR and DPR. But is has different result for sample of Thailand, the result show that the sustainability report disclosure positively influences CR, but it has no significant effect on ROA and DPRKeywords : Sustainability report, Profitability, Liquidity, Dividend Payout Ratio